PENGARUH MODEL SCIENCE ENVIRONMENT TECHNOLOGY SOCIETY (SETS) BERMUATAN ETNOSAINS TERHADAP PENGUASAAN KONSEP SISWA PADA MATERI LINGKUNGAN - Rikizaputra Rikizaputra; Arlian Firda; Safira Safira; Mega Elvianasti (Universitas Lancang Kuning, 2023)
Environmental learning that contains ethnoscience or local wisdom really needs to be implemented in the classroom in terms of culture and science that students can understand, for learning it is necessary to use appropriate learning models, one of which is the SETS model. This study aims to determine the effect of the SETS model on students' mastery of concepts in biology material. This research was conducted at SMAN 13 Pekanbaru in the 2021/2022 Academic Year. The population in this study were students of class X with a sample of class X4 as the experimental class (using the SETS model) and X5 as the control class (conventional learning) taken by simple random sampling technique. Quasi-experimental research, with the matching only pretest posttest control group design. Data collection through pretest, posttest and observation. In the research results, it was found that the average N-Gain in the control class was 0.25 (low), while in the experimental class it was 0.51 (medium). The results of the N-Gain t-test showed a significant difference between control and experimental class mastery of concepts. Thus it can be concluded that learning the SETS model.